A novel oral vaccine delivery system for enhancing stability and immune protection: bacterium-like particle with functional coating - De, Xinqi; Gao, Mingchun; Jia, Zheng; Ren, Hongkun; Liu, Runhang; Zhou, Xinyao; Guo, Junjie; Wang, Jiaqing; Yu, Qi; Qu, Nanzhu; Wang, Fang; Ge, Junwei (Frontiers in Microbiology, 2024)
Bacterium-like particles (BLPs) have gained significant attention in vaccine development due to their potential as effective immune enhancers and antigen delivery systems. BLPs are generated by boiling lactic acid bacteria in an acidic solution and are devoid of proteins and nucleic acids, offering advantages in terms of ease of preparation, high safety, and good stability. Furthermore, by employing protein anchor (PA), heterogeneous antigens can be efficiently displayed on the surface of BLPs, resulting in enhanced delivery effectiveness. Despite these benefits, most BLP-based vaccines are currently administered via injection or intranasal delivery, with oral delivery remaining limited. This limitation is primarily due to the harsh environment of the gastrointestinal tract, which degrades the antigens displayed on the surface of these particles. To enhance the efficacy of oral immunization with subunit vaccines, we developed a simple and rapid method for self-assembling a lipid membrane onto the surface of BLPs vaccines, achieving an encapsulation efficiency of up to 99%, and the combination has good biosafety. The novel oral delivery system not only preserves the adjuvant activity of BLPs but also efficiently protects antigens from adverse gastrointestinal environments, increasing the absorption of the vaccine in intestinal Peyer’s patches (PPs). Oral immunization was required only once, and protection after the challenge was up to 100%. Furthermore, we observed rapid immunity and cross-protection. Transcriptome analysis of the small intestine suggested that immune enhancement probably be exerted by promoting the absorption and transport of antigens. Therefore, we posit that the design of this new oral delivery system presents a novel approach to advancing the development of oral subunit vaccines.